Virus Transfer at the Skin–Liquid Interface - Pitol, A. K; Bischel, Heather N; Kohn, Tamar; Julian, Timothy R (Environmental science & technology, 2017)
Understanding virus transfer between liquid and skin is necessary to estimate transmission during water-related activities. Here, we modeled virus transfer from liquid-to-skin and skin-to-liquid. We performed human subject studies using three bacteriophages as pathogenic virus surrogates: nonenveloped MS2 and Qβ and enveloped Φ6. Our study shows that transfer from liquid-to-skin is describable by a single model based on (1) virus concentration and (2) volume of liquid remaining on skin. Contact times (0.1–30 min), and virus species had little-to-no influence on virus transfer. Likewise, liquid conditions (pH 6–9, ionic strength 10–550 mM) had no influence on transfer as shown for MS2. The model accounts for both, virus adsorbed onto the skin, and virus in the liquid retained on skin. In comparison, virus transfer from skin-to-liquid was influenced by the wetness of the skin and by liquid type (water, saliva). 90 ± 19% of the virus inoculated on the skin are transferred to the water when the skin remains wet compared to 30 ± 17% when the skin is dry. The transfer from skin-to-liquid was 41% higher when the recipient liquid was water as compared with saliva. This study quantifies virus transfer between liquid and skin and guides risk assessments of water-related activities.